Survivable controller placement in software defined network - Ahmad Moradi; Ali AbdiSeyedkolaei (AUT Journal of Mathematics and Computing, 2022)
One of the problems raised in software defined networks is to deter[1]mine the number and installation location of controllers so that the cost of implementation reduced and survivability of the network against link or node failure increased. Current investigation in SDN imposes full mesh topology in order to connect controllers. This approach while incurring a huge installation cost, dose not carefully incorporate network survivability requirements. In this paper, we improve an existing integer programming approach to a novel model so as to effectively address user defined survivability requirements. Computational results reported also reveals that our models could be solved by state-of-the-art MIP solvers like CPLEX within a reasonable time limit.